Enantioselectivity-Evaluation of Chiral Copper(II) Complexes Coordinated by Novel Chiral Tetradentate Ligands for Free Amino Acids by Mass Spectrometry Coupled With the Isotopically Labeled Enantiomer Method - Nakakoji, Takashi; Yoshino, Kaori; Izutsu, Kazuki; Sato, Hirofumi; Miyake, Hiroyuki; Mieda, Eiko; Shinoda, Satoshi; Tsukube, Hiroshi; Kawasaki, Hideya; Arakawa, Ryuichi; Ono, Daisuke; Shizuma, Motohiro (Frontiers in Chemistry, 2020)
Chiral copper(II) complexes with chiral tetradentate ligands, which are N,N-ethylene-bridged bis(S-amino acid amide or ester) prepared from S-alanine, S-phenylalanine, S-valine or S-proline, generated in methanol. The copper complexes made three component complexes with free chiral amino acid as the second ligand enantioselectively. The enantioselectivity was evaluated by electrospray ionization-mass spectrometry coupled with the deuterium-labeled enantiomer method. These copper complexes showed high enantioselectivity for free amino acids having bulky side chains, suggesting that steric interaction is a major factor in chiral recognition. The copper complex with chiral ligand prepared from S-proline showed opposite enantioselectivity to copper complexes with ligands from other S-amino acids. The conformational difference of the tetradentate ligand in the copper complex was found to be significant for enantioselectivity.